Implementasi Efektivitas Layanan Whatsapp Web Pada Pembayaran Pajak Kendaraan Bermotor Studi Kasus Di Kota Batam - Faizin, Teguh; -, Herman (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2024)
To increase PKB and SWDKLLJ and to increase public compliance in paying taxes, an innovation is needed to remind the public not to be in arrears in paying motor vehicle taxes. A reminder application is needed that is integrated with the WhatsApp Blast API which will then send notifications of tax due dates or other SAMSAT information based on the mobile phone number that was registered when purchasing the first motor vehicle. This research method uses Scrum to collect and analyze the effectiveness of the application when implemented in the community, with this application it can be utilized optimally so that it can minimize arrears and increase community compliance in paying taxes.